Superb Fairy-Wren (Malurus cyaneus) Sons and Daughters Acquire Song Elements of Mothers and Social Fathers - Evans, Christine; Kleindorfer, Sonia (Frontiers in Ecology and Evolution, 2016)
Birdsong is regarded as a classic example of a sexually-selected trait and has been primarily studied in systems with male song. Complex solo female song is emerging from the shadows of overlooked phenomena. In males, rearing conditions affect male song complexity, and males with complex songs are often more successful at mate attraction and territorial defense. Little is known about the ontogeny or function of complex female song. Here we examine song elements in fledgling superb fairy-wrens (Malurus cyaneus) in relation to the song elements of adult tutors. Male and female superb fairy-wrens produce solo song year-round to defend a territory. We ask if sons and daughters acquire song elements from sex-specific vocal tutors. We found that sons and daughters produced the song elements of their mothers and social fathers, and that sons and daughters had comparable song element repertoires at age 7–10 weeks. We conclude that sons and daughters increase their song element repertoire when vocally imitating elements from several vocal tutors, and that both sexes acquire elements from male and female vocal tutors in this system.